Novel FRET-Based Src Biosensor Reveals Mechanisms of Src Activation and Its Dynamics in Focal Adhesions. Issue 2 (21st February 2019) - Koudelková, Lenka; Pataki, Andreea Csilla; Tolde, Ondřej; Pavlik, Vojtech; Nobis, Max; Gemperle, Jakub; Anderson, Kurt; Brábek, Jan; Rosel, Daniel
Summary: Src kinase plays an important role in a multitude of fundamental cellular processes and is often found deregulated in tumors. Active Src adopts an open conformation, whereas inactive Src is characterized by a very compact structure stabilized by inhibitory intramolecular interactions. Taking advantage of this spatial regulation, we constructed a fluorescence resonance energy transfer (FRET)-based Src biosensor and analyzed conformational changes of Src following Src activation and the spatiotemporal dynamics of Src activity in cells. We found that activatory mutations either in regulatory or kinase domains induce opening of the Src structure. Surprisingly, we discovered that Src inhibitors differ in their effect on the Src structure, some counterintuitively inducing an open conformation. Finally, we analyzed the dynamics of Src activity in focal adhesions by FRET imaging and found that Src is rapidly activated during focal adhesion assembly, and its activity remains steady and high throughout the life cycle of focal adhesion and decreases during focal adhesion disassembly. Graphical Abstract: Highlights: FRET-based Src biosensor was developed and functionally verified Src activatory mutations induce opening of Src structure Src inhibitors differentially affect Src structure and its cellular localization Src activity is high in FAs and increases/decreases during FA assembly/disassembly Abstract : Koudelková et al. developed and functionally verified a Src kinase biosensor. The biosensor represents a unique tool to monitor Src structure, activity, and localization both in vitro and in cells. Using the biosensor, the action of Src inhibitors and Src dynamics in focal adhesions was described.